BLENDED LEARNING BERBASIS EDMODO TERHADAP EFEKTIVITAS PEMBELAJARAN BIOLOGI: KAJIAN META-ANALISIS - Reni Alfionora; Ardi Ardi; Rahmawati Darussyamsu (Jurnal Biolokus: Jurnal Penelitian Pendidikan Biologi dan Biologi, 2021)
The rapid development of science and technology has made many changes in the field of education, including innovations that make it easier for teachers and students in learning activities. One of the innovations in the field of education is the blended learning model. A blended learning model that combines the advantages of face-to-face learning with distance learning to make learning activities more effective. One of the platforms that can be used in blended learning is edmodo. This platform combines social communication with learning so that learning activities can also be monitored properly by parents of students. This research was conducted to see how the effect of the blended learning model using the Edmodo platform on the effectiveness of learning biology. The research was carried out using a systematic literature analysis method known as meta-analysis. Data were obtained from 20 articles and processed using the effect size formula. Based on the analysis and discussion that has been carried out, the results obtained are 1,01 with a high category. Therefore, it can be concluded that the use of edmodo has a high influence on the effectiveness of learning biology.